Transformasi Karakteristik Arsitektur Modern Pada Fasad Porola Grand Renggali Hotel Takengon - Siska; Dafrina, A; Andriani, D (Jurnal MESIL (Mesin Elektro Sipil), 2025)
Takengon City is a city in Aceh Province, which is located in the Gayo highlands, Central Aceh. The city of Takengon is known for its natural beauty, Lut Tawar Lake, and the richness of Gayo culture, including its superior coffee production. The development of tourism in the Takengon area, Central Aceh has also encouraged the growth of supporting infrastructure, including the hotel sector. There are many accommodation or hotel buildings in Central Aceh, one of the properties that stands out is the Portola Grand Renggali Hotel Takengon. Infrastructure such as hotels continues to develop with the times. including the Portola Grand Renggali Hotel Takengon which is known to have undergone a transformation process. The use of form follows function theory, which states that the form of a building is based on its function, to analyze the transformation of hotel architecture through facade elements. likely influenced by function, needs, or user expectations. In addition, the principle "God Is In The Detail" is also relevant, emphasizing that the quality of design lies in attention to small details that influence the overall aesthetic. The aim of this research is to investigate how elements can change contemporary architectural characteristics in the case study analysis, a qualitative descriptive approach was used. The final output of this research is the conclusion drawn from a study of how the facade elements of the portola grand renggali hotel takengon have changed the characteristics of contemporary architecture.